Characterization of the dnaK Multigene Family in the Cyanobacterium Synechococcus sp. Strain PCC7942 - Nimura, Kaori (American Society for Microbiology, 2001)
The cyanobacterium Synechococcus sp. strain PCC7942 has three dnaK homologues (dnaK1, dnaK2, and dnaK3), and a gene disruption experiment was carried out for each dnaK gene by inserting an antibiotic resistance marker. Our findings revealed that DnaK1 was not essential for normal growth, whereas DnaK2 and DnaK3 were essential. We also examined the effect of heat shock on the levels of these three DnaK and GroEL proteins and found a varied response to heat shock, with levels depending on each protein. The DnaK2 and GroEL proteins exhibited a typical heat shock response, that is, their synthesis increased upon temperature upshift. In contrast, the synthesis of DnaK1 and DnaK3 did not respond to heat shock; in fact, the level of DnaK1 protein decreased. We also analyzed the effect of overproduction of each DnaK protein in Escherichia coli cells using an inducible expression system. Overproduction of DnaK1 or DnaK2 resulted in defects in cell septation and formation of cell filaments. On the other hand, overproduction of DnaK3 did not result in filamentous cells; rather a swollen and twisted cell morphology was observed. When expressed in an E. coli dnaK756 mutant, dnaK2 could suppress the growth deficiency at the nonpermissive temperature, while dnaK1 and dnaK3 could not suppress this phenotype. On the contrary, overproduction of DnaK1 or DnaK3 resulted in growth inhibition at the permissive temperature. These results suggest that different types of Hsp70 in the same cellular compartment have specific functions in the cell.